Seismic activity characteristics in the East Sea area - Hoan, Vu Thi; Lu, Ngo Thi; V., Rodkin M.; Quang, Nguyen; Huong, Phan Thien (Vietnam Journal of Earth Sciences, 2018)
In this paper, seismic activity characteristics in the East Sea area was analyzed by authors on the base of the unified earthquake catalog (1900-2017), including 131505 events with magnitude 3 ≤ Mw ≤ 8.4. The seismic intensity in the East Sea during the period 1900-2017 is characterized by the earthquake representative level Mw = 4.7. The strong earthquake activity in the East Sea area clearly shows the regularity in each stage. In the period from 1900 to 2017, the East Sea area has four periods of strong earthquake activity, each stage is nearly 30 years with particular characteristics. The distribution of the maximum earthquake quantities by years has a cyclicity in all four periods. In each stage there are 1-2 strong earthquakes with Mmax ≥ 8.0. The strong earthquakes with Mmax ≥ 7.5 have occurred by a repeatable rule of 3-5 years in all four stages. This allows the prediction of the maximum earthquake repeat cycle of Mmax ≥ 7.5 in the study area is 3-5 years. In other hand, the maximum magnitude values for the East Sea region has assessed by GEV method with several different predict periods (20, 40, 60, 80, 100 years), with predicted probability 80%. We concluded that it is possible that earthquake have Mmax = 8.7 will occur in next 100 years.ReferencesBautista C.B., Bautista M.L.P., Oike K., Wu F.T., Punongbayan R.S., 2001. A new insight on the geometry of subducting slabs in northern Luzon, Philippines. Tectonophysics, 339, 279-310.Bui Cong Que, et al., 2010. Seismic and tsunamis hazard in coastal Viet Nam. Natural Science and Technology Publishing House, 311p.Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Pham Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La-Bac Yen fault zone. J. Sci. of the Earth, 35, 53-59 (in Vietnamese).Cao Dinh Trieu, Pham Nam Hung, 2008. Deep-seated fault zone presents the risk of strong earthquakes in the East and South Vietnam Sea. Scientific Report of the First National Conference on Marine Geology, Ha Long, October, 9-10, 491-497.Hsu Ya-Ju, Yu Shui Ben, Song Teh.-Ru Alex, Bacolcol Teresito, 2012. Plate coupling along the Manila subduction zone between Taiwan and northern Luzon.  J. Asian Earth Sci., 51, 98-108.http://www.ioc-tsunami.org/index.php?option=com_oe&task=viewDocumentRecord&docID=16478.http://www.jcomm.info/index.php?option=com_oevàtask=viewDocumentRecordvafdocID=16484.Kirby S., Geist E., Lee W.H., Scholl D., Blakely, R., October 2005. 660 Tsunami source characterization for western Pacific subduction 661 zones: a perliminary report. Report, USGS Tsunami Subduction 662 Source Working Group.Le Huy Minh, Frederic Masson, Alain Bourdiilon, Patrick Lassudrie Duchesne, Rolland Fleury, Jyr-ching Hu, Vu Tuan Hung, Le Truong Thanh, Nguyen Chien Thang, Nguyen Ha Thanh, 2014. GPS data continuously in Vietnam and Southeast Asia. J. Sci. of the Earth, 36, 1-13.Le Van De, 1986. Outline of tectonics of the East Vietnam sea and adjacent areas. Proc. 1st Conf. Geol. Indoch., Ho Chi Minh City, 397-404, Hanoi.Ngo T.L., Tran V.P., 2013. Development of a new algorithm for the separation of seismic and anemone groups from the earthquake list to ensure the independence of events. Journal of Marine Science and Technology, Hanoi, 13(3A), 79-85.Nguyen Dinh Xuyen., et al., 2007. Report on the implementation of the task "Earthquake scenarios for tsunamis in the South China Sea". Institute of Meteorology and Hydrology.Nguyen Hong Phuong, 2015. Estimation of seismic hazard parameters for potential tsunami genic sources in the South China Sea region.Nguyen Hong Phuong, 2001. Probabilistic Seismic Hazard Assessment Along the Southeastern Coast of Vietnam, Natural Hazards, 24, 53-74.Nguyen Hong Phuong, 2004. Earthquake risk map of Vietnam and East Sea. J. Sci. of the Earth, 26, 97-111.Nguyen Hong Phuong, Bui Cong Que, 2012. Investigation of earthquake tsunami sources, capable of affecting Vietnamese coast, Nat Hazards, 64, 311-327.Nguyen Hong Phuong, Pham The Truyen, 2014. Probabilistic Seismic Hazard Assessment for the South Central Vietnam. J. Sci. of the Earth, 36, 451-461.Nguyen Van Luong, Bui Cong Que, Nguyen Van Duong, 2008. Tectonic stresses and modern movements in the crust of the Earth in the East Sea area, Journal of Marine Science and Technology, 46-52.Nguyen Van Luong, Duong Quoc Hung, Bui Thi Thanh and Tong Duy Cuong, 2003. Characteristics of fault systems in the East Sea area. J. Sci. of the Earth., 25, 1-8 (in Vietnamese).Nguyen Van Luong, et al., 2002. Result of establishment of the list of earthquake dynamics in the East Sea area, studies on geology and marine geophysics, VII, Hanoi.Nguyen Van Luong, et al., 2008. Tectonic seismic and geodynamic features of the South China Sea, Proceedings of the 1st National Conference on Marine Geology and Sustainable Development, 9-10, Ha Long, 498-509.Pham Van Thuc and Nguyen Thi Kim Thanh, 2004. Earthquake zone in the South China Sea and coastal areas. Journal of Geology, A series, 285, 11-12.Pham Van Thuc, 2001, Characteristics of tsunamis in the East Sea region of Vietnam. TC and CNN, TI, 2, 52-64.Phan Trong Trinh,  Ngo Van Liem, Vy Quoc Hai, John Beavan, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Nguyen Quang Xuyen, Nguyen Dang Tuc, Dinh Van Thuan, Nguyen Trong Tan, Nguyen Viet Thuan, Le Huy Minh, Bui Thi Thao. Nguyen Huy Thinh, Dinh Van The, Le Minh Tung, Tran Quoc Hung, Nguyen Viet Tien, 2010b. Modern tectonic movement in the East Sea and surrounding areas. Journal of Geology. Series A, 320, 9-10, Hanoi.Phan Trong Trinh, 2006. The Tsunami and December 26, 2004 in the Indian Ocean: A Warning to Vietnam. Journal of Geology, Series A, 293, Hanoi.Phan Trong Trinh, et al., 2010a. Research on the tectonic activity, modern tectonics and geodynamics of the South China Sea as a scientific basis for forecasting the types of catastrophe involved and proposed solutions prevent. KC.09.11/06-10. Institute of Geology, 446p.Phan Trong Trinh, Nguyen Van Huong, Ngo Van Liem, Tran Dinh To, Vy Quoc Hai, Hoang Quang Vinh, Bui Van Thom, Nguyen Quang Xuyen, Nguyen Viet Thuan, Bui Thi Thao, 2011. Geological and geological hazards in Vietnam's sea and nearby. J. Sci. of the Earth, 33, 443-456.Pisarenko V.F., Sornette A., Sornette D. and Rodkin M.V, 2008. New approach to the Characterization of Mmax and of the Tail of the Distribution of Earthquake Magnitudes. Pure and Applied Geophysics, 165, 847-888.Pisarenko V.F, Sornette D. and Rodkin M.V., 2010. Distribution of maximum Earthquake magnitudes in future time intervals: application to the seismicity of Japan (1923-2007). EPS (Earth, Planets and Space), 62, 567-578.Pisarenko V.F., Rodkin M.V, and Rukavishnikova T.A., 2014. Estimation of the Probability of Strongest Seismic Disasters Based on the Extreme Value Theory. Physics of the Solid Earth, 50(3), 311-324.Pisarenko V.F., Rodkin M.V. and et al., 2012. New general quantile approach to the seismic rick assessment application to the Vietnam region. //Proceedings of the International Conference on "Geophysics - Cooperation and Sustainable Development." Science and Technology Publishing House. Hanoi, 161-167.Vu Thanh Ca, 2008. Report on the project to build a map of tsunami warning for coastal areas of Vietnam. Institute of Hydrometeorology and Environment - Ministry of Natural Resources and Environment.Yingchun Liu, Angela Santos, Shuo M. Wang, Yaolin Sh, Hailing Liu, David A. Yuen, 2007. Tsunami hazards along Chinese coast from potential earthquakes in the South China Sea. Phys. Earth Planet. Interiors, 163, 233-244.Zhiguo Xu, 2015. Seismicity and Focal mechanisms in the South China Sea Region and its Tectonic Significances.